Genomic prediction and genome-wide association study for dagginess and host internal parasite resistance in New Zealand sheep. (December 2015) - Pickering, Natalie; Auvray, Benoit; Dodds, Ken; McEwan, John
Abstract Background Dagginess (faecal soiling of the perineum region) and host nematode parasite resistance are important animal welfare traits in New Zealand sheep. Genomic prediction (GP) estimates the genetic merit, as a molecular breeding value (mBV), for each trait based on many SNPs. The additional information the mBV provides (as determined by its accuracy) has led to its incorporation into breeding schemes. Some GP methods give SNP effects, which provide additional information to identify genome-wide associations (GWAS) for a trait of interest. Here we report results from a GP and GWAS study for dagginess and host nematode parasite resistance in a New Zealand sheep industry resource. Results Genomic prediction analysis was performed using 50K SNP chip data and parent average-removed, de-regressed BVs for five traits, from a resource of 8705 pedigree recorded animals. The five traits were dag score at three and eight months (DAG3, DAG8) and nematode faecal egg count in summer (FEC1), autumn (FEC2) and as an adult (AFEC). The resource consisted of Romney, Coopworth, Perendale, Texel and various breed crosses (designated: CompRCP, CompRCPT and CompCRP). The pure breeds, apart from Texel, plus CompRCP were used to develop the GP. The resulting SNP effects were used to identify genetic regions associated with dagginess and parasite resistance. Accuracies of the weighted correlation between mBV and true BV ranged between −0.07 (Texel) and 0.56 (Coopworth) for DAG3 and DAG8. For FEC1, FEC2 and AFEC accuracies ranged between −0.22 (CompRCPT) and 0.69 (Coopworth). The weighted average individual accuracy (calculated from theory) ranges were 0.13 (Texel) to 0.52 (Coopworth) and 0.11 (Texel) to 0.55 (Coopworth) respectively, for dagginess and parasite traits. There was one SNP for DAG8 that reached Bonferroni significance threshold (P  < 1 × 10−6 ) on OAR15, the same two SNPs for each of the parasite traits (OAR26) and none for DAG3. A notable peak was also observed on OAR7 for all the parasite traits, however, it did not reach the Bonferroni significance threshold. Conclusions This study presents the first results of a GWAS on dagginess and faecal egg count traits in New Zealand sheep. The results suggest that there are quantitative trait loci on OAR 15 for dagginess and on OAR26 and seven for faecal egg count.